Metabolomics Reveal Altered Postprandial Lipid Metabolism After a High-Carbohydrate Meal in Men at High Genetic Risk of Diabetes. Issue 6 (2nd May 2019) - Adamska-Patruno, Edyta; Samczuk, Paulina; Ciborowski, Michal; Godzien, Joanna; Pietrowska, Karolina; Bauer, Witold; Gorska, Maria; Barbas, Coral; Kretowski, Adam
ABSTRACT: Background: The transcription factor 7-like 2 ( TCF7L2 ) gene confers one of the strongest genetic predispositions to type 2 diabetes, but diabetes development can be modified by diet. Objective: The aim of our study was to evaluate postprandial metabolic alterations in healthy men with a high genetic risk of diabetes, after two meals with varying macronutrient content. Methods: The study was conducted in 21 homozygous nondiabetic men carrying the high-risk (HR, n = 8, age: 31.2 ± 6.3 y, body mass index (BMI, kg/m 2 ) 28.5 ± 8.1) or low-risk (LR, n = 13, age: 35.2 ± 10.3 y, BMI: 28.1 ± 6.4) genotypes at the rs7901695 locus. During two meal challenge test visits subjects received standardized isocaloric (450 kcal) liquid meals: high-carbohydrate (HC, carbohydrates: 89% of energy) and normo-carbohydrate (NC, carbohydrates: 45% of energy). Fasting (0 min) and postprandial (30, 60, 120, 180 min) plasma samples were analyzed for metabolite profiles through untargeted metabolomics. Metabolic fingerprinting was performed on an ultra-high-performance liquid chromatography (UHPLC) system connected to an iFunnel quadrupole-time-of-flight (Q-TOF) mass spectrometer. Results: In HR-genotype men, after the intake of an HC-meal, we noted a significantly lower area under the curves (AUCs) of postprandial plasma concentrations of most of the phospholipids (−37% to −53%, variable importance in the projection (VIP) = 1.2–1.5), lysophospholipids (−29% to −86%, VIP = 1.1–2.6), sphingolipids (−32% to −47%, VIP = 1.1–1.3), as well as arachidonic (−36%, VIP = 1.4) and oleic (−63%, VIP = 1.3) acids, their metabolites: keto- and hydoxy-fatty acids (−38% to −78%, VIP = 1.3–2.5), leukotrienes (−65% to −83%, VIP = 1.4–2.2), uric acid (−59%, VIP = 1.5), and pyroglutamic acid (−65%, VIP = 1.8). The AUCs of postprandial sphingosine concentrations were higher (125–832%, VIP = 1.9–3.2) after the NC-meal, AUCs of acylcarnitines were lower (−21% to −61%, VIP = 1.1–2.4), and AUCs of fatty acid amides were higher (51–508%, VIP = 1.7–3.1) after the intake of both meals. Conclusions: In nondiabetic men carrying the TCF7L2 HR genotype, subtle but detectable modifications in intermediate lipid metabolism are induced by an HC-meal. This trial was registered at www.clinicaltrials.gov as NCT03792685.